Death of hardship - Inyang, Ekpe (Langaa Research & Pub. CIG, 2012)
"Death of hardship kaleidoscopically unveils human intrigues, predicaments and woes. It brings into sharp focus the most dreaded products of cruel oppression, exploitation, and destruction -- the worst forms of human degradation and sufferings. However, it also sheds beams of hope, celebrating optimism in the struggle and eventually opening the curtain to the stage of victory of the oppressed and impoverished under the shameless sky"--Back cover.